2017
DOI: 10.1155/2017/2376893
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Autophagy Activation and Increased Apoptosis Are Associated with Palmitic Acid-Induced Cardiomyocyte Insulin Resistance

Abstract: Diabetic cardiomyopathy (DCM) remains the major cause of death associated with diabetes. Researchers have demonstrated the importance of impaired cardiac insulin signaling in this process. Insulin resistance (IR) is an important predictor of DCM. Previous studies examining the dynamic changes in autophagy during IR have yielded inconsistent results. This study aimed to investigate the dynamic changes in autophagy and apoptosis in the rat H9c2 cardiomyocyte IR model. H9c2 cells were treated with 500 μM palmitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 45 publications
2
23
0
Order By: Relevance
“…In addition, the expression levels of glycolytic enzymes (GCK, PFK, and PK), p-GSK3β/GSK3β, and lipolytic enzymes (PPARα) were upregulated, whereas hepatic gluconeogenic enzymes (G-6-P and PEPCK) and fatty-acid synthesis enzymes (SREBP-1c) were decreased after HucMDE treatment in T2DM rats and in PAinduced L-O2 cells, indicating that HucMDEs alleviated glucose and lipid metabolism dysfunction both in vivo and in vivo. Autophagy is a lysosomal degradative process through which misfolded proteins and damaged organelles are sequestered, degraded, and recycled [37]. Previous studies have shown that induction of autophagy in hepatocytes increases insulin sensitivity, suggesting that enhanced autophagy might represent a mechanism for promoting insulin responses and, thus, treating diabetes [38].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the expression levels of glycolytic enzymes (GCK, PFK, and PK), p-GSK3β/GSK3β, and lipolytic enzymes (PPARα) were upregulated, whereas hepatic gluconeogenic enzymes (G-6-P and PEPCK) and fatty-acid synthesis enzymes (SREBP-1c) were decreased after HucMDE treatment in T2DM rats and in PAinduced L-O2 cells, indicating that HucMDEs alleviated glucose and lipid metabolism dysfunction both in vivo and in vivo. Autophagy is a lysosomal degradative process through which misfolded proteins and damaged organelles are sequestered, degraded, and recycled [37]. Previous studies have shown that induction of autophagy in hepatocytes increases insulin sensitivity, suggesting that enhanced autophagy might represent a mechanism for promoting insulin responses and, thus, treating diabetes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the results showed that chloroquine pretreatment significantly attenuated oxalate-induced cell viability inhibition and oxidative injury, whereas rapamycin exerted contrasting effects, indicating that autophagy activation has detrimental effects on cells exposed to oxalate, these results are opposite to the results of urinary proteins, cisplatin and cyclosporine A exposure. In one hand, autophagy was found to proceed cell apoptosis and injury under a low level of injury via clearing the degradation of damaged subcellular organelles, whereas severe injury-induced excessive autophagy activation may be detrimental [35] , [36] , [37] . In another hand, the effect of autophagy activation on cell death and injury is related to its duration.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we didn’t analysis the insulin sensitivity in endothelial cell, but we demonstrated that argirein ameliorated systemic insulin sensitivity in the diabetic rats. Actually, it was well-known that insulin resistance is accompanied by the increases in apoptosis in different cells which is associated with diabetic complication 38 , 39 . Our previous study also demonstrated that argirein blunted hepatosteatosis through normalizing apoptosis and insulin resistance in the diabetic liver 8 .…”
Section: Discussionmentioning
confidence: 99%